Tantangan dan Peluang Pembiayaan Syariah Non-Bank dalam Meningkatkan Kesejahteraan Masyarakat - Dicky Octaviano; Dhea Puspa Ayu Nanda; Mohamad Maula Asy’ari; Arief Safari; Amelia Amelia (Lembaga Pengembangan Kinerja Dosen, 2024)
Non-bank Islamic financing has a strategic role in supporting financial inclusion and improving the welfare of the Indonesian people. This study analyzes the challenges and opportunities of non-bank Islamic financing, focusing on Islamic cooperatives, Baitul Maal wat Tamwil (BMT), and Islamic fintech platforms. A descriptive qualitative approach based on literature study is used to explore the historical dimensions, structural challenges, strategic opportunities, and socio-economic impacts of this sector. The results show that this sector faces major obstacles, such as low Islamic financial literacy (below 10%), limited regulations, and lack of technological adaptation. However, significant opportunities arise from the development of financial technology, government policy support, and increasing global awareness of sustainable finance. Islamic principles, such as profit sharing and social justice, are advantages that can empower micro, small, and medium enterprises (MSMEs) and remote communities. This study recommends strategies to overcome the challenges, including increasing financial literacy through digital education, strengthening innovative regulations, and utilizing Islamic-based technology. Cross-sector collaboration and human resource development are also key elements to support the growth of this sector. The contribution of the research lies in a holistic analytical framework to understand the dynamics of non-bank Islamic financing, as well as strategic recommendations to optimize its potential. Thus, this sector is expected to be a driving force for inclusive and sustainable economic development in Indonesia.